2015
DOI: 10.1007/s00381-015-2843-y
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and compression distraction osteogenesis based on volumetric and neurodevelopmental analysis in sagittal craniosynostosis

Abstract: Symmetric sagittal synostosis can be treated comprehensively through DO in combination with expansion and compression procedures. ICV and HC measurements were useful for designing surgical and postoperative distraction strategies. Achievement of mesocephalic CI and neurodevelopmental improvement validated morphological and functional effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Our recent data are consistent with these findings regarding intracranial volume. A smaller preoperative intracranial volume might suggest a low developmental score compared to the normal volume, although in most cases, the volume was not smaller than the age-matched average 25) .…”
Section: The Relationship Between Distortion Of Skull and Cognitive Fmentioning
confidence: 88%
See 2 more Smart Citations
“…Our recent data are consistent with these findings regarding intracranial volume. A smaller preoperative intracranial volume might suggest a low developmental score compared to the normal volume, although in most cases, the volume was not smaller than the age-matched average 25) .…”
Section: The Relationship Between Distortion Of Skull and Cognitive Fmentioning
confidence: 88%
“…However, a consistent association between neurodevelopmental status, optimal age for surgery, and intracranial pressure (ICP) has not been observed in isolated single suture craniosynostosis (SSC). Ongoing research and accumulating evidence suggest that the results of neurodevelopmental examination of isolated SSC children are mostly within the normal range 25) . However, the proportion of scores that are below average is greater for these children than in children with patent sutures, suggesting an elevated risk of developmental delays and further cognitive deterioration 16 23 24 25) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the frame could be removed under 60 days after surgery in our institution. Recent reports of conventional unilateral distraction osteogenesis methods showed that the period from the first surgery of attachment of the device to the second surgery of removal ranged from 70 to 100 days ( Table 2 ) 23 31 34 37 39 41) .…”
Section: Advantages Of Mcdo Compared With the Other Types Of Distractmentioning
confidence: 99%
“…Our mean surgical time was approximately 300 minutes, even in cases from 2011. Recent reports of the various unidirectional distraction osteogenesis procedures showed that the mean surgical times ranged from 115 to 230 minutes ( Table 2 ) 23 31 34 37 39) . Our relatively longer surgical time may depend on the time of osteotomy to create many smaller bone fragments.…”
Section: Limitations Of Mcdomentioning
confidence: 99%